Accuracy and reliability of magnetic resonance imaging in the diagnosis of idiopathic intracranial hypertension - ULUÇ, KAYIHAN; ÇİMŞİT, NURİ ÇAGATAY; ILGIN, CAN; DERİCİOĞLU, VOLKAN; KAHRAMAN KOYTAK, PINAR (My University, 2022)
© 2022 Elsevier B.V.Purpose: To determine the diagnostic utility of brain magnetic resonance imaging (MRI) findings in patients with idiopathic intracranial hypertension (IIH) and to investigate the significance of evaluating radiological findings together with neurological and ophthalmological data in the diagnosis of IIH. Materials and Methods: All consecutive patients diagnosed with IIH in our tertiary neuro-ophthalmology center between January 1, 2018 and March 15, 2020, were included in the study. The clinical, radiological, and ophthalmological findings of IIH patients were compared with the control group with similar demographic characteristics. Results: A total of 98 patients, 49 cases and 49 controls, were included in the study. Lateral ventricular index had the highest area under the curve (AUC) value (0.945) for prediction of disease group followed by sella height category (AUC = 0.915) and optic nerve tortuosity (AUC = 0.855) According to the multivariate model we developed, caudate index (OR = 0.572, 95% CI 0.329–0.996), lateral ventricle index (OR = 3.969, 95% CI 1.851–8.509) and bilateral optic nerve tortuosity (OR = 22,784, 95% CI 2.432–213.450) were significant predictors for disease group. Conclusion: Tortuosity in the optic nerve, lateral ventricular index and caudate index can be used as MRI parameters supporting the diagnosis of IIH in clinically suspicious cases. A holistic approach to the clinical and radiological findings of the cases in the diagnosis of IIH can prevent overdiagnosis and enable early correct diagnosis.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; Diagnostic accuracy; Idiopathic intracranial hypertension; Lumbar puncture; Magnetic resonance imaging; Pseudotumor cerebri